ANALISIS TERHADAP HUBUNGAN INDUSTRIAL ATAS PEMUTUSAN HUBUNGAN KERJA SEPIHAK (Studi Putusan No. 248/pdt.sus-PHI/2019/PN.MDN) - Rizqi, Muhammad (IBLAM LAW REVIEW, 2022)
The case of termination of employment is not a difficult case to find. One of the cases of Termination of Employment that occurred was the case of the Industrial Relations Dispute in the Medan District Court between the insurance company PT. Kresna Life Insurance against William Winata as the supervisory position holder, with decision number 248/Pdt.Sus- PHI/2019/PN. Mdn. On July 22, 2017 William Winata sent a letter addressed to PT. Kresna Life Insurance regarding the review of the contents of the mutation warrant which at the core of the application is willing to be transferred by asking for a mutation fee but does not receive a response and the Defendant's bipartite request is also ignored so that the bipartite is considered a failure, the mutation made by the Defendant is a fraudulent mutation that very forced to avoid obligations and responsibilities for employee rights due to changes in the Agency System. The purpose of this study is to find out the legal rules in Indonesia regarding unilateral termination of employment by the company, to determine the inhibiting factors for the implementation of the IRC decision, and to determine the legal analysis of the termination of employment by the company in the decision number 248/pdt.sus-PHI/ 2019/pn.mdn.The research conducted is normative legal research with a sociological juridical approach (empirical) which is taken from secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials.Based on the research, it is understood that Decision Number 248/Pdt.Sus- PHI/2019/Pn.Mdn is a decision whose lawsuit value is below Rp.150,000,000 so that all charges for the case are borne by the government. The inhibiting factors for the implementation of the decision are generally due to the limited budget from the government to finance the execution and the uncertainty of the time period when the execution costs will be disbursed. In the decision of the Industrial Relations Court in the case of Termination of Employment (PHK) which orders employers to pay for the rights of workers who are laid off, such a decision can be executed or implemented because it is condemnatoir or punishment. There is a possibility that the entrepreneur will not implement the decision to pay for the rights of the worker/laborer. If theentrepreneur does not implement such a decision, the entrepreneur has committed an unlawful act.Keywords: Industrial Relations, Layoffs, Insurance Companies